ANALISIS PENGARUH SUMBERDAYA ORGANISASI, KEWIRAUSAHAAN, TEKNOLOGI DAN FOREX RATE TERHADAP KINERJA EKSPOR INDUSTRI TEKSTIL DAN PRODUK TEKSTIL (TPT) INDONESIA - Sinaga, Dadjim (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 2007)
This research studies the influence company resources (organization, enterprenuership, technology) and forex rate perception to export performance of textile industry and textile product in Indonesia. The Research object is to examine 60 industrial company of TPT in Banten (West Java) and DKI Jakarta. The result of the research indicates that simultanly independent variable (company resources and Forex rate) can predict probability the dependent variable - export performance 63, 4 %, and the rest of 36,4 % by other factor which is not include in this research.Parsially, the resources in technology and organization cannot predict exporting performance probability, because regresion model from each variable are not signifiqant, namely, 0, 116 > 0,05 and 0,636 > 0,05 (real level 5%). However, entreprenuership and perception regarding forex rate can predict export performance probability, at the value of signifiqancy to both variable namely, each of them equal to 0, 00 < 0, 05.This research is expected can be benefit to TPT industry for improving the global market competitiveness, and also for researchers in area company resources and forex rate related to development of theory and related to company manufacture competitiveness in global market.